Yield, tuber quality, and disease incidence on potato crop as affected by silicon leaf application - Soratto, Rogério Peres; Fernandes, Adalton Mazetti; Crusciol, Carlos Alexandre Costa; Souza-Schlick, Genivaldo David de (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the effects of silicon leaf application, in the form of stabilized silicic acid, on the disease incidence, yield, and quality of potato. Three experiments were carried out: one with the cultivar Agata and another with Atlantic, in Botucatu, SP, Brazil; and one with the cultivar Agata, in Itaí, SP. A randomized complete block design was used, with eight replicates. The treatments consisted of: a control (without Si) and Si foliar spraying at 2 L ha‑1 of a commercial product containing 0.8% of soluble Sias concentrated, stabilized silicic acid. The silicon dose was split in four applications during the crop cycle.Silicon application reduces the severity of late blight and the incidence of blackleg, besides increasing tuberyield and tuber dry matter content. Leaf‑supplied silicon increases potato tuber yield, regardless of its effecton disease incidence.